George Piper Dances and Russell Maliphant Company Review - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2002)
PALABRAS CLAVE: Torsion, George Piper Dances, Russell Maliphant Company, William Trevitt, Michael Nunn, Ballet Boyz.
Dentro del apartado "Dance Now. The Place To Be. Dance in London".